Streamlined Description of Pontics - Mir, Shazia; Mir, Fozia; Naqash, Talib Amin (Journal of Orofacial Research, 2013)
Advances in the field of restorative materials allow a lost tooth to be replaced by artificial tooth structure that is virtually indiscernible from the original. Pontics are the artificial teeth ina fixed partial prosthesis that replace the lost natural teeth, and restore function and appearance. A wide variety of names have been attributed to pontics by different authors. Classification systems were devised based on the nomenclature. Other than the definition there is no universality of the nomenclature, classification and indications. This greatly confuses the professionals in the decision making process of fixed prosthodontic treatment. The aim of this review is to evaluate the descriptions given in the literature and comprehend them under a common heading.